Contribution of Bioethics in the Formation of the Pedagogical Knowledge of the Health Professional (Docentes 2.0 Journal, 2025)
As a science, bioethics deepens the study of bioethical principles and their application. It is considered a branch of ethics due to its notable relevance to life and society. This research explored integrating bioethical principles into developing pedagogical knowledge among healthcare professionals at the UCV School of Dentistry. This research was conducted within the humanistic paradigm, using the hermeneutic method, a qualitative approach, a narrative design, an interpretive design, and a cross-sectional approach. The sample comprised 10 faculty members from the Central University of Venezuela School of Dentistry. The data collection technique used was interviews. The data obtained was analyzed qualitatively, and the relevant findings from the technique were interpreted. The integration of bioethical principles influences the development of pedagogical knowledge among healthcare professionals by providing an ethical framework to guide their practice. As these principles become integrated into education and training, positive changes in healthcare are likely to occur in the future.
Keywords: Bioethics; pedagogy; knowledge; training; health